Changing sociolinguistic identities of young, middle-class 'Coloured' people in post-apartheid Cape Town - Dennis, Tracey Lynn (Linguistics, 2023)
This study set out to examine the sociolinguistics of social change amongst a group ofyoung, middle-class coloured people who were educated in a predominantly white school environment. The demise of the apartheid system in the early 1990s led to a situation in which racial mixing in government-run schools was permitted for the first time. I conducted sociolinguistic interviews with 20 self-identified 'coloured' Cape Town residents, who attended schools that were formerly open only to white children. . I analysed the data on two levels. Firstly, an analysis of accent, focusing on three salient phonetic markers of South African English, namely the GOOSE, BA TH and PRICE lexical sets (Wells 1982). Acoustic analysis of these vowels was done using a computer software programme, Praat, to record a total of 4410 tokens for the 20 speakers. The second level of analysis investigated how the informants constructed social identities in those unprecedented educational circumstances. I used three theories of identity to do this: Speech Accommodation Theory (Giles 1973), Social Identity Theory (Tajfel 1972) and the Linguistic Market (Bourdieu and Boltanski 1975). Comparing the results of the phonetic and sociological analyses, I found that the two levels of analysis supported the same conclusion: the young, coloured people in the sample subscribe to a coloured social identity, but have clear links with the white community. This suggests that they occupy an intermediate space between the two race groups, which is not surprising given the significant contact they had with members of both communities. There is some evidence of a separation between the coloured community and the typical 'coloured' accent, however, suggesting that one does not need to sound 'typically coloured' in order to be part of the coloured community. It is likely that we are witnessing the formation of an upper middle-class within the coloured middle-class community.